66-7x=11x+18

Simple and best practice solution for 66-7x=11x+18 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 66-7x=11x+18 equation:


Simplifying
66 + -7x = 11x + 18

Reorder the terms:
66 + -7x = 18 + 11x

Solving
66 + -7x = 18 + 11x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-11x' to each side of the equation.
66 + -7x + -11x = 18 + 11x + -11x

Combine like terms: -7x + -11x = -18x
66 + -18x = 18 + 11x + -11x

Combine like terms: 11x + -11x = 0
66 + -18x = 18 + 0
66 + -18x = 18

Add '-66' to each side of the equation.
66 + -66 + -18x = 18 + -66

Combine like terms: 66 + -66 = 0
0 + -18x = 18 + -66
-18x = 18 + -66

Combine like terms: 18 + -66 = -48
-18x = -48

Divide each side by '-18'.
x = 2.666666667

Simplifying
x = 2.666666667

See similar equations:

| x*2-5=3 | | 37-4*7= | | 8a+5b=2b-5a | | 2x+92=9x-13 | | x^4-4x^3=40+17x | | -4+x-3x-7=-33 | | x^4-4x^3-17x=40 | | p^4-16q^4= | | 3x+2+5x=45 | | -3y=-7-x | | x-3y+7=0 | | 2+2X^3=0 | | 2x+1+x=-14 | | -10+x+7x=62 | | x^2+4x-41=4 | | z+3(z-4)=5 | | 70=4x+2x+10 | | 2+4x-2x=14 | | 6-3x-6x=42 | | 32a-8=-30a | | d=7h+12 | | 8*a^2+3a-800=0 | | 8*a^2+3a+800=0 | | 2x^3-6x^2+5x+6=0 | | -12h+30=-4h-17 | | 4x=5y+33 | | 15-(5-x)=1 | | 6(1-7k)=40-8k | | 3+2v=-6v+3 | | 2*log(x^2)+log(x-1)=0 | | 2logx^2+logx-1=0 | | 3(p+7)=-33 |

Equations solver categories